Preparation method and application of metal-doped calcium manganese ore manganese dioxide

By doping appropriate metal active ions into calmanganite manganese dioxide (τ-MnO2) and synthesizing by hydrothermal method, the problems of doping large-sized metal ions lead to amorphization of τ-MnO2 and collapse of tunnel structures are solved, and the electrochemical performance of τ-MnO2 in aqueous zinc ion batteries is improved.

CN119551727APending Publication Date: 2025-03-04SUZHOU CITY UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411733462.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, when doping large-size metal ions in calmandeite manganese dioxide (τ-MnO2), it is easy to cause amorphization of τ-MnO2 and collapse of tunnel structure, affecting its electrochemical performance.

Method used

By doping metal active ions such as Zn2+, Co2+, Ni2+, Al3+, Fe3+, Eu3+, etc. into τ-MnO2, the hydrothermal method is used to synthesize it to ensure that the binding of the doped ions and τ-MnO2 does not change its tunnel structure.

Benefits of technology

It effectively improves the electrochemical performance of τ-MnO2 in aqueous zinc ion batteries, improves the stability and activity of the material, and enhances the cycling performance and specific capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551727A_ABST
    Figure CN119551727A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of metal-doped calcium manganese ore manganese dioxide. The method comprises the following steps: dissolving manganese salt in deionized water to prepare a solution; under stirring, dropwise adding an alkali solution into the obtained solution, after a solid is separated out, adding metal salt and magnesium sulfate, uniformly mixing, then slowly adding an oxidizing agent, and stirring to obtain a black precipitate; washing the black precipitate with water, soaking the black precipitate in a magnesium chloride solution, washing again, transferring the obtained solid and magnesium chloride into a high-pressure kettle with a polytetrafluoroethylene lining, heating, cooling, centrifuging, washing and drying the obtained precipitate to obtain metal-doped calcium manganese ore manganese dioxide; the original tunnel structure of the calcium manganese ore manganese dioxide cannot be changed by doping the ions such as Zn < 2 + >, Co < 2 + >, Ni < 2 + >, Al < 3 + >, Fe < 3 + > and Eu < 3 + > into the calcium manganese ore manganese dioxide, the doped metal active ions can be combined with the calcium manganese ore manganese dioxide, the electrochemical performance of the material in the water-based zinc ion battery can be effectively improved, and the material has important significance on research of the water-based zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a preparation method and application of metal-doped calcite manganese dioxide. Background Art

[0002] In order to solve the safety and environmental problems caused by the widespread use of lithium-ion batteries today, aqueous zinc-ion batteries, as a safer, more economical and more environmentally friendly alternative, have received increasing research attention in the past decade. Aqueous zinc-ion batteries (ZIBs) have the advantages of high volumetric energy density and low cost, and are the most promising large-scale energy storage devices. Aqueous zinc-ion batteries use neutral (or slightly acidic) aqueous solutions as electrolytes, which have faster ion conduction rates than organic electrolytes. The aqueous characteristics also make ZIBs easy to assemble in the air, giving them the advantages of environmental protection, high safety and low cost.

[0003] The positive electrode is a key component of ZIBs, usually providing active sites for zinc storage and largely determining the potential and capacity of the battery, which has an important impact on battery performance. Several common ZIBs positive electrode materials mainly include manganese-based compounds, vanadium-based compounds, Prussian blue and its analogs. The specific capacity of Prussian blue analogs is low (less than 70 mAh g -1 ), prone to oxidation at high potentials, and rapid attenuation of specific capacity during cycling; vanadium-based materials have high synthesis costs, high toxicity, low average operating voltages, and are prone to collapse after repeated cycles, leading to vanadium dissolution, limiting their commercial viability in ZIB technology. Manganese-based oxides have larger channel sizes and higher theoretical capacities, and have multiple oxidation states of +2, +3, and +4, including MnO2, Mn3O4, Mn2O3, MnO2, etc. Among them, MnO2 with an oxidation state of +4 has higher stability, and MnO2 has multiple crystal forms that can maintain charge balance related to multiple electron transfer reactions.

[0004] The modification work of manganese-based compounds mainly includes defect engineering, doping engineering and pre-intercalation. Ion doping is an effective way to improve the electrochemical properties of materials. By introducing foreign ions to break the equilibrium state of the inherent material, change the lattice configuration of the material, or improve the embedding and extraction of ions, the structural properties of the material are improved by causing significant changes in the electronic structure, and finally the selective optimization of physical and chemical properties is achieved, so that the material has specific value and use.

[0005] Manganese dioxide is one of the cathode materials currently being studied in zinc-ion batteries due to its low price, low toxicity, environmental friendliness, rich phases, diverse morphologies, and simple regulation. Due to the diversity of morphological structures and synthesis methods, MnO2 with different morphologies and structures can be designed and synthesized. Among the many one-dimensional tunnel-structured MnO2 crystal forms, τ-MnO2 is composed of three chains of edge-sharing [MnO6] octahedrons, with a larger tunnel size of (3×3) tunnel structure, which can accommodate some metal ions (Zn 2+ ,Mg 2+ , Fe 3+ The τ-MnO2 cathode material with tunnel structure was synthesized by hydrothermal method (the tunnel structure diagram is shown in Figure 1 As shown), active ions (such as Zn 2+ ,Co 2+ , Ni 2+ , Al 3+ , Fe 3+ ,Eu 3+ The electrochemical performance of τ-MnO2 can be improved by modifying the active ions of τ-MnO2 (such as τ-MnO2, ... etc.), which is of great significance to the research of positive electrode materials for aqueous zinc-ion batteries. Due to the low cost and environmental friendliness of MnO2, τ-MnO2 doping with active ions is expected to become a new technology to improve the performance of positive electrode materials for zinc-ion batteries.

[0006] At present, studies have shown that doping with certain large-sized metal ions will cause serious amorphization of τ-MnO2, resulting in the collapse of the τ-MnO2 tunnel structure, affecting the combination of doped active ions with τ-MnO2, and ultimately making it impossible to effectively improve its electrochemical performance. The tunnel space of τ-MnO2 is supported by hydrated magnesium ions. Due to charge balance, τ-MnO2 has a higher Mn 3+ and oxygen defect content, which is beneficial to the oxygen evolution reaction (OER) activity, and τ-MnO2 has a higher BET surface area and theoretically has better OER activity. However, some studies have found that 3+ τ-MnO2 with higher oxygen defect content and higher BET surface area did not show better activity. This may be due to the large radius and lower mobility of hydrated Mg 2+ The ions create a distinct shell within the tunnel, shielding the electrochemically active sites and hindering charge transport on τ-MnO2. Therefore, it is urgent to provide a method that can effectively improve the electrochemical performance of this material in aqueous zinc-ion batteries. Summary of the invention

[0007] At present, studies have shown that when the size is larger than Mn 4+ / Mn 3+The doping of metal atoms into the τ-MnO2 lattice will cause lattice strain and structural reconstruction, and the tighter the MnO2 lattice is arranged, the greater the lattice strain will be, which will cause serious amorphization and disorder of τ-MnO2, resulting in the collapse of the τ-MnO2 tunnel structure, affecting the combination of doped active ions with τ-MnO2, and ultimately making it impossible to effectively improve its electrochemical performance.

[0008] In order to solve the above problems, the present invention provides a preparation method and application of metal-doped calcite manganese dioxide. 2+ ,Co 2+ , Ni 2+ , Al 3+ , Fe 3+ ,Eu 3+ Plasma will not change the original tunnel structure of τ-MnO2. The doped metal active ions can combine with τ-MnO2, which can effectively improve the electrochemical performance of the material in aqueous zinc-ion batteries. This is of great significance to the research of aqueous zinc-ion batteries.

[0009] The present invention is achieved through the following technical solutions:

[0010] The first object of the present invention is to provide a method for preparing metal-doped calcite manganese dioxide, comprising the following steps:

[0011] (1) dissolving a manganese salt in deionized water to prepare a solution;

[0012] (2) under stirring, adding the alkaline solution dropwise to the solution obtained in step (1), after solid is precipitated, adding metal salt and magnesium sulfate and mixing evenly, then slowly adding oxidant and stirring to obtain a black precipitate;

[0013] (3) washing the black precipitate obtained in step (2) with water and then immersing it in a magnesium chloride solution, washing it again with water and transferring the obtained solid together with the magnesium chloride to a polytetrafluoroethylene-lined autoclave for heating, cooling it and then centrifuging it, washing the obtained precipitate, and drying it to obtain metal-doped calcite manganese dioxide;

[0014] In step (2), the metal salt includes one or more of zinc salts, cobalt salts, nickel salts, aluminum salts, europium salts, iron salts and lanthanide metal salts.

[0015] In one embodiment of the present invention, in step (1), the manganese salt is selected from one or more of manganese sulfate monohydrate, manganese chloride and manganese nitrate.

[0016] In one embodiment of the present invention, in step (2), the oxidant is selected from potassium persulfate and / or ammonium persulfate.

[0017] In one embodiment of the present invention, in step (2), the alkali in the alkali solution is sodium hydroxide / potassium hydroxide, ammonia water, etc.

[0018] In one embodiment of the present invention, the zinc salt includes one or more of zinc acetate, zinc chloride, zinc nitrate and zinc sulfate;

[0019] and / or, the cobalt salt comprises one or more of cobalt nitrate, cobalt chloride and cobalt sulfate;

[0020] And / or, the nickel salt includes one or more of nickel acetate, nickel chloride and nickel sulfate;

[0021] and / or, the aluminum salt comprises aluminum chloride and / or aluminum nitrate;

[0022] And / or, the europium salt includes one or more of europium nitrate, europium chloride, europium sulfate and europium acetate;

[0023] And / or, the iron salt includes one or more of ferric chloride, ferric nitrate, ferric acetate and ferric sulfate.

[0024] In one embodiment of the present invention, the mass ratio of the manganese salt to the alkali in the alkali solution is 1:4 to 3:1;

[0025] And / or, the molar ratio of the manganese salt to the metal salt is 4:1 to 20:1.

[0026] In one embodiment of the present invention, in step (3), the heating conditions are: heating at 120° C. to 200° C. for 20 h to 100 h.

[0027] The second object of the present invention is to provide metal-doped calcite manganese dioxide obtained by the preparation method.

[0028] The third object of the present invention is to provide the use of the metal-doped calcium manganese ore manganese dioxide in the preparation of an aqueous zinc ion battery positive electrode or an aqueous zinc ion battery.

[0029] The fourth object of the present invention is to provide an aqueous zinc ion battery positive electrode, comprising the metal-doped calcium manganese ore manganese dioxide.

[0030] The fifth object of the present invention is to provide an aqueous zinc ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the positive electrode of the aqueous zinc ion battery.

[0031] In one embodiment of the present invention, the method for preparing the metal-doped calcite manganese dioxide comprises the following steps:

[0032] (1) dissolving manganese sulfate monohydrate in deionized water to prepare a solution;

[0033] (2) under stirring, adding an alkaline solution dropwise to the solution obtained in step (1), after solids are precipitated, adding metal salts and magnesium sulfate and mixing evenly, then slowly adding potassium persulfate and stirring to obtain a black precipitate; the alkali of the alkaline solution is sodium hydroxide, potassium hydroxide, ammonia water, etc.;

[0034] (3) The black precipitate obtained in step (2) is washed with water and then immersed in a magnesium chloride solution. After washing again with water, the obtained solid is transferred together with the magnesium chloride to a polytetrafluoroethylene-lined autoclave for heating, cooled and then centrifuged. The obtained precipitate is washed and dried to obtain metal-doped calcite manganese dioxide.

[0035] The above technical solution of the present invention has the following advantages compared with the prior art:

[0036] (1) The present invention provides a preparation method and application of metal-doped calcite manganese dioxide. In the present invention, a τ-MnO2 material doped with an active metal is synthesized by a hydrothermal method. The method is simple and effective, and the material synthesis process is simple, pollution-free, and green.

[0037] (2) The τ-MnO2 material doped with active metals prepared by the present invention still maintains the original tunnel structure of τ-MnO2 after being doped with metal ions, and the introduction of metal ions does not cause the generation of metal or metal oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0039] Figure 1 is the XRD diffraction spectrum of Eu-τ-MnO2 in the present invention;

[0040] Figure 2 It is the charge and discharge curve of Eu-τ-MnO2 at 0.1C rate in the present invention;

[0041] Figure 3 It is the cycle performance of the Eu-τ-MnO2 zinc ion battery at 0.1C rate in the present invention;

[0042] Figure 4 is a SEM image of Eu-τ-MnO2 of the present invention;

[0043] Figure 5 is the XRD diffraction spectrum of Fe-τ-MnO2 in the present invention;

[0044] Figure 6 It is the cycle performance of the Fe-τ-MnO2 zinc ion battery in the present invention at a rate of 0.1C. DETAILED DESCRIPTION

[0045] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0046] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0047] The present invention provides a τ-MnO2 positive electrode material doped with metal active ions and having a tunnel structure synthesized by a hydrothermal method, wherein the material is prepared by the following method:

[0048] Example 1 Zn 2+ Synthesis of doped τ-MnO2

[0049] 0.9g of manganese sulfate monohydrate was dissolved in 10mL of deionized (DI) water to prepare solution A, 3.5g of sodium hydroxide was dissolved in 15mL of deionized water to prepare solution B, and then solution B was added dropwise to solution A under stirring. After all solids were precipitated, 1.0g of zinc acetate and 0.1g of magnesium sulfate were mixed and slowly added to the above solution, and then 0.9g of potassium persulfate was slowly added and stirred for 2 hours. The obtained black precipitate was washed with a large amount of deionized water, and then soaked in 48.0g of magnesium chloride (500mL) solution for 24 hours. After washing with deionized water, the obtained solid was transferred to a 50mL polytetrafluoroethylene-lined autoclave together with 30mL, 1mol / L magnesium chloride, and heated in an oven at 180°C for 24 hours. After cooling, the precipitate was collected by centrifugation and washed three times and once with deionized water and ethanol respectively. Dry in an oven at 60°C to collect the final product Zn-τ-MnO2.

[0050] Example 2Co 2+ Synthesis of doped τ-MnO2

[0051] 0.9g of manganese sulfate monohydrate was dissolved in 10mL of deionized (DI) water to prepare solution A, 3.5g of sodium hydroxide was dissolved in 15mL of deionized water to prepare solution B, and then solution B was added dropwise to solution A under stirring. After all solids were precipitated, 0.2g of cobalt nitrate and 0.1g of magnesium sulfate were mixed and slowly added to the above solution, and then 0.9g of potassium persulfate was slowly added and stirred for 2 hours. The obtained black precipitate was washed with a large amount of deionized water and then soaked in a 48.0g magnesium chloride (500mL) solution for 24 hours. After washing with deionized water, the obtained solid was transferred to a 50mL polytetrafluoroethylene-lined autoclave together with 30mL, 1mol / L magnesium chloride and heated in an oven at 180°C for 24 hours. After cooling, the precipitate was collected by centrifugation and washed three times and once with deionized water and ethanol respectively. Dry in an oven at 60°C and collect the final product Co-τ-MnO2.

[0052] Example 3A1 3+ Synthesis of doped τ-MnO2

[0053] 0.9g of manganese sulfate monohydrate was dissolved in 10mL of deionized (DI) water to prepare solution A, 3.5g of sodium hydroxide was dissolved in 15mL of deionized water to prepare solution B, and then solution B was added dropwise to solution A under stirring. After all solids were precipitated, 0.3g of aluminum nitrate and 0.1g of magnesium sulfate were mixed and slowly added to the above solution, and then 0.9g of potassium persulfate was slowly added and stirred for 2 hours. The obtained black precipitate was washed with a large amount of deionized water, and then soaked in 48.0g of magnesium chloride (500mL) solution for 24 hours. After washing with deionized water, the obtained solid was transferred to a 50mL polytetrafluoroethylene-lined autoclave together with 30mL, 1mol / L magnesium chloride, and heated in an oven at 180°C for 24 hours. After cooling, the precipitate was collected by centrifugation and washed three times and once with deionized water and ethanol respectively. Dry in an oven at 60°C to collect the final product Al-τ-MnO2.

[0054] Example 4Eu 3+ Synthesis of doped τ-MnO2

[0055] 0.9g of manganese sulfate monohydrate was dissolved in 10mL of deionized (DI) water to prepare solution A, 3.5g of sodium hydroxide was dissolved in 15mL of deionized water to prepare solution B, and then solution B was added dropwise to solution A under stirring. After all solids were precipitated, 0.2g of europium nitrate and 0.1g of magnesium sulfate were mixed and slowly added to the above solution, and then 0.9g of potassium persulfate was slowly added and stirred for 2 hours. The obtained black precipitate was washed with a large amount of deionized water and then soaked in 48.0g of magnesium chloride (500mL) solution for 24 hours. After washing with deionized water, the obtained solid was transferred to a 50mL polytetrafluoroethylene-lined autoclave together with 30mL, 1mol / L magnesium chloride and heated in an oven at 180°C for 24 hours. After cooling, the precipitate was collected by centrifugation and washed three times and once with deionized water and ethanol respectively. Dry in an oven at 60°C to collect the final product Eu-τ-MnO2. The XRD diffraction spectrum and SEM image of the product Eu-τ-MnO2 are shown in Figure 1 and Figure 4 As shown by Figure 1 and Figure 4 It can be seen that τ-MnO2 was successfully synthesized, and Eu doping did not destroy the original morphology and structure of τ-MnO2.

[0056] Example 5Fe 3+ Synthesis of doped τ-MnO2

[0057] Dissolve 0.9g of manganese sulfate monohydrate in 10mL of deionized (DI) water to prepare solution A, and dissolve 3.5g of sodium hydroxide in 15mL of deionized water to prepare solution B. Then, add solution B dropwise to solution A under stirring. After all solids are precipitated, mix 0.1g of ferric chloride and 0.1g of magnesium sulfate evenly and slowly add them to the above solution. Then slowly add 0.9g of potassium persulfate and continue stirring for 2 hours. Wash the obtained black precipitate with a large amount of deionized water, and then soak it in 48.0g of magnesium chloride (500mL) solution for 24 hours. After washing with deionized water, transfer the obtained solid together with 30mL, 1mol / L magnesium chloride to a 50mL polytetrafluoroethylene-lined autoclave and heat it in an oven at 180°C for 24 hours. After cooling, collect the precipitate by centrifugation and wash it three times and once with deionized water and ethanol respectively. Dry it in an oven at 60°C and collect the final product Fe-τ-MnO2. The XRD diffraction spectrum of the product Fe-τ-MnO2 is as follows Figure 5 As shown by Figure 5 It can be seen that τ-MnO2 was successfully synthesized.

[0058] Test Case

[0059] The products obtained in Example 4 and Example 5 were transferred into small centrifuge tubes with acetylene black respectively. Use a pipette to draw (200 μL 5% PVDF) reagent and drop it into the above centrifuge tube. The centrifuge tube filled with reagents was placed in a small ball mill for ball milling (400 rpm). The ball milling was adjusted by drawing 100 μL NMP reagent each time using a pipette until the slurry viscosity was moderate. The ball-milled slurry was spread on a stainless steel foil into uniform strips, and a coater with a thickness of 50 μm to 100 μm was used for uniform coating. The coated slurry was transferred to a 60°C oven for drying for 24 hours to prepare a MnO2 positive electrode material. The dried MnO2 positive electrode material was cut into circular electrodes with a diameter of 1.3 cm using a manual slicer for use in zinc ion battery positive electrodes.

[0060] The charge and discharge curve of Eu-τ-MnO2 at 0.1C rate is shown in Figure 2 As shown by Figure 2 It can be seen that during the cycle, H + / Zn 2+ Continuously insert the Eu-τ-MnO2 positive electrode.

[0061] The cycling performance of Eu-τ-MnO2 zinc ion battery at 0.1C rate is shown in Figure 3 As shown by Figure 3 It can be seen that after 15 cycles, it can reach about 300 mAh g -1 Stable specific capacity.

[0062] The cycling performance of Fe-τ-MnO2 zinc ion battery at 0.1C rate is shown in Figure 6 As shown by Figure 6 It can be seen that due to the activation process of the Fe-τ-MnO2 electrode during the cycle, the specific capacity shows an increase phenomenon and can reach about 145 mAh g after 40 cycles. -1 Stable specific capacity.

[0063] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing metal-doped calcite manganese dioxide, characterized in that: The following steps are involved: (1) dissolving a manganese salt in deionized water to prepare a solution; (2) under stirring, adding the alkaline solution dropwise to the solution obtained in step (1), after solid is precipitated, adding metal salt and magnesium sulfate and mixing evenly, then slowly adding oxidant and stirring to obtain a black precipitate; (3) washing the black precipitate obtained in step (2) with water and then immersing it in a magnesium chloride solution, washing it again with water and transferring the obtained solid together with the magnesium chloride to a polytetrafluoroethylene-lined autoclave for heating, cooling it and then centrifuging it, washing the obtained precipitate, and drying it to obtain metal-doped calcite manganese dioxide; In step (2), the metal salt includes one or more of zinc salts, cobalt salts, nickel salts, aluminum salts, europium salts, iron salts and lanthanide metal salts.

2. The preparation method according to claim 1, characterized in that: In step (1), the manganese salt is selected from one or more of manganese sulfate monohydrate, manganese chloride and manganese nitrate.

3. The preparation method according to claim 1, characterized in that: In step (2), the oxidant is selected from potassium persulfate and / or ammonium persulfate.

4. The preparation method according to claim 1, characterized in that: The zinc salt includes one or more of zinc acetate, zinc chloride, zinc nitrate and zinc sulfate; and / or, the cobalt salt comprises one or more of cobalt nitrate, cobalt chloride and cobalt sulfate; And / or, the nickel salt includes one or more of nickel acetate, nickel chloride and nickel sulfate; and / or, the aluminum salt comprises aluminum chloride and / or aluminum nitrate; And / or, the europium salt includes one or more of europium nitrate, europium chloride, europium sulfate and europium acetate; And / or, the iron salt includes one or more of ferric chloride, ferric nitrate, ferric acetate and ferric sulfate.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the manganese salt to the alkali in the alkali solution is 1:4 to 3:1; And / or, the molar ratio of the manganese salt to the metal salt is 4:1 to 20:

1.

6. The preparation method according to claim 1, characterized in that: In step (3), the heating conditions are: heating at 120°C to 200°C for 20h to 100h.

7. The metal-doped calcite manganese dioxide obtained by the preparation method according to any one of claims 1 to 6.

8. Use of the metal-doped calcium manganese ore manganese dioxide according to claim 7 in preparing an aqueous zinc ion battery positive electrode or an aqueous zinc ion battery.

9. A positive electrode for an aqueous zinc ion battery, characterized in that: The invention comprises the metal-doped calcium manganese ore manganese dioxide as described in claim 7.

10. An aqueous zinc ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is the aqueous zinc ion battery positive electrode according to claim 9.

Citation Information

Cited By

  • Phenolic aldehyde substance and manganese dioxide composite type positive electrode active material as well as preparation method and application thereof

    CN121172096A